Dentinogenesis Imperfekta : Aspek Genetika Molekular, Klasifikasi dan Upaya Penanggulangannya - Elza Ibrahim Auerkari; A. Surjadi; S. Mangoendjaja (Faculty of Dentistry, Universitas Indonesia, 2015)
Dentinogenesis Imperfecta (DI) is a hereditary simple autosomal dominant disorder showing abnormalities in the dentin of developing teeth and occuring at a rate of about 1 in 8000 births affecting both primary and secondary dentitions. The expression of DI shows a high penetrance and a low mutation rate. Two main types of DI appear to exist: type 1 which is the defect associate with osteogenesis imperfecta, and type II which is the classical hereditary opalescent dentin. The formerly proposed DI type III appears to be only a modified expression of the same gene as in the classical DI type II. This paper reviews molecular genetic aspects of DI.